Current progress of cerebral organoids for modeling Alzheimer's disease origins and mechanisms - Sai Sreenivasamurthy; Mahek Laul; Nan Zhao; Tiffany Kim; Donghui Zhu (Wiley, 2023)
Abstract Alzheimer's disease (AD) is a progressive, neurodegenerative disease that has emerged as a leading risk factor for dementia associated with increasing age. Two‐dimensional (2D) cell culture and animal models, which have been used to analyze AD pathology and search for effective treatments for decades, have significantly contributed to our understanding of the mechanism of AD. Despite their successes, 2D and animal models can only capture a fraction of AD mechanisms due to their inability to recapitulate human brain‐specific tissue structure, function, and cellular diversity. Recently, the emergence of three‐dimensional (3D) cerebral organoids using tissue engineering and induced pluripotent stem cell technology has paved the way to develop models that resemble features of human brain tissue more accurately in comparison to prior models. In this review, we focus on summarizing key research strategies for engineering in vitro 3D human brain‐specific models, major discoveries from using AD cerebral organoids, and its future perspectives.